2018
DOI: 10.21873/anticanres.12537
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Pulmonary Function Tests (PFTs) and Outcomes from Resected Early Stage Non-small Cell Lung Cancer (NSCLC)

Abstract: Preoperative PFTs did not predict for survival from resected early-stage NSCLC, but did predict for prolonged hospital stay following surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…DLCO reflects the capillary surface area available for gas diffusion. Preoperative DLCO has been demonstrated to predict the risk of complications, short- and long-term outcomes and the length of hospitalization in patients undergoing thoracic surgery [ 21 ]. The meta-analysis showed a lower degree of DLCO decrease in the segmentectomy group, indicating that it had better preservation of oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…DLCO reflects the capillary surface area available for gas diffusion. Preoperative DLCO has been demonstrated to predict the risk of complications, short- and long-term outcomes and the length of hospitalization in patients undergoing thoracic surgery [ 21 ]. The meta-analysis showed a lower degree of DLCO decrease in the segmentectomy group, indicating that it had better preservation of oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that all lung cancer patients who are candidates for surgery should have pulmonary function tests (PFTs), because the parameters of PFTs are very useful for lung cancer preoperative risk assessments [8,9]. More than that, in recent years, emerging studies suggested that valuable PFT parameters might also play a role in predicting prolonged p-LOS following lung resection: Some suggested inspiratory capacity (IC) and some suggested forced expiratory volume in 1 s (FEV 1 ) or diffusion capacity for carbon monoxide (DLCO) [10,11]. Currently, it is still worthy to unveil more optimal or novel predictors among these various PFTs for better prediction of prolonged p-LOS after lung cancer surgery.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…However, the predictive capabilities of these factors were poor. Moreover, poor pulmonary function, as determined by the PFT, was not associated with low morbidity or mortality in patients undergoing VATS for lung cancer surgery (11,12). Berry et al (13) concluded that preoperative PFT was associated with PPCs after lung cancer surgery only in thoracotomy, but not in VATS.…”
Section: Discussionmentioning
confidence: 99%